Chile : Financial Sector Assessment Program-Technical Note on Systemic Liquidity. (IMF Staff Country Reports; Country Report ;, 2022)
Chile is characterized by a highly interconnected financial system, which presents risks and opportunities for the development of liquidity markets. On the one hand, the large domestic non-bank financial sector (pension funds, mutual funds, insurers) creates a large investor base for domestic debt securities, fostering the development of these markets. On the other hand, the non-bank financial sector is vulnerable to shocks which may have significant spillovers to funding markets and to the banking system.